2020
DOI: 10.3390/ani10060989
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Common Recovery Blood Sampling Methods, in Mice (Mus Musculus), on Well-Being and Sample Quality: A Systematic Review

Abstract: Blood sampling is often performed in laboratory mice. Sampling techniques have the potential to cause pain, distress and impact on lifetime cumulative experience. In spite of institutions commonly providing guidance to researchers on these methods, and the existence of published guidelines, no systematic evaluation of the evidence on this topic exists. A systematic search of Medline, Scopus, and Web of Science was performed, identifying 27 studies on the impact of recovery blood sample techniques on mouse welf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…There are several points of relevance here in relation to MGS construct validity. Firstly, the blood sampling interventions applied are likely to produce momentary pain as opposed to no pain [ 83 ], so evidence of a change actually supports construct validity. Secondly, tail handling has been suggested to be aversive rather than painful [ 84 ], so an effect does call into question the specificity of the scale for pain (although it is worth noting that a previous study found no effect of handling [ 57 ]).…”
Section: Discussionmentioning
confidence: 99%
“…There are several points of relevance here in relation to MGS construct validity. Firstly, the blood sampling interventions applied are likely to produce momentary pain as opposed to no pain [ 83 ], so evidence of a change actually supports construct validity. Secondly, tail handling has been suggested to be aversive rather than painful [ 84 ], so an effect does call into question the specificity of the scale for pain (although it is worth noting that a previous study found no effect of handling [ 57 ]).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that one mouse had a particularly high FCM level in the early phase, corresponding to a loss of more than 10% body weight. Compared to other mice, this mouse had more intraoperative loss of blood, which may have contributed to its significant weight loss and stress [ 28 ]. This observation also indicates that the performance of the surgeon has the biggest effect on the animal’s well- being.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies are likely due to the fact that the cited studies differ in details of the applied technique as well as the frequency of blood sampling, and the time point after the procedure that the physiological and behavioural changes were assessed. Thus, sound evidence is still needed to make valid recommendations regarding appropriate and most welfare-friendly blood sampling techniques [27].…”
Section: Introductionmentioning
confidence: 99%